EMPIRE AND POPULAR CULTURE. ([S.l.])
1 online resource
Keywords: From 1830, if not before, the Empire began to permeate the domestic culture of Empire nations in many ways. From consumables, to the excitement of colonial wars, celebrations relating to events in the history of Empire, and the construction of Empire Day in the early Edwardian period, most citizens were encouraged to think of themselves not only as citizens of a nation but of an Empire. Much of the popular culture of the period presented Empire as a force for civilisation' but it was often far from the truth and rather, Empire was a repressive mechanism designed ultimately tobenefit white settlers and the metropolitan economy. This four volume collection on Empire and Popular Culture contains a wide array of primary sources, complemented by editorial narratives which help the reader to understand the significance of the documents contained therein. It is informed by the recent advocacy of a three-nation' approach to Empire containing documents which view Empire from the perspective of England, Scotland and Wales and will also contain material produced for Empire audiences, as well as indigenous perspectives. The sources reveal both the celebratory and the notorious sides of Empire. These volumes focus on institutions and popular culture such as clubs, societies, missions, churches, educational institutions and the ways in which people were depicted in popular culture - from heroic explorers to the fascination with and racism towards, indigenous peoples across the long nineteenth century.